Dropped! - Kuipers, Alice, 1979- (Orca anchor., 2024)
"Dex is dropped onto a deserted tropical island to be a player in a social media competition. Dex is one of six contestants on Dropped!, an internet reality show. He's glad to escape his real life after being dumped by his girlfriend, Lola, and destroying his social life. He and the other contenders have to spend five days on a deserted island, and the person who gains the most likes and followers will be the winner. The prize is a ton of money and status as an influencer. Keeping people watching is the challenge, and Dex will do whatever it takes. He needs to win--it's the only way to get Lola and his popularity back. But on the island, away from his ex, he finds himself flirting with the gorgeous and popular Amina. When Dex keeps placing behind Amina, he realizes he has to be more daring to get the engagements he needs. But how extreme will he need to be? And is it worth it to win?"--Publisher's website.